DOMINASI LAKI-LAKI DALAM POLITIK INDONESIA: HAMBATAN MENUJU KETERCAPAIAN REPRESENTASI SUBSTANTIF PEREMPUAN DI PARLEMEN - Hizkia Sitompul; Bintang Caroline Ginting; Eileen Regina Anggita Br Pelawi; Ibnu Umar Ramadhan; Sahru Azkiya Putra Ramadhan; Siti Anadea; Ria Manurung; Silvia Annisa (JURNAL ILMIAH PENELITIAN MAHASISWA, 2025)
This research analyzes the failure of women's substantive representation in the Indonesian parliament, focusing on the 2019 post-election period. It uses a multi-method qualitative method that includes literature study, content analysis, and critical discourse analysis. The sources of this research study include news articles from national online media for the 2019-2023 period, and relevant scientific journals. Among the important indicators analyzed, there is a significant difference between the level of women's representation in the legislature (20.9% in the House of Representatives) and the 30% quota target, the strategic placement of female candidates in elections, and the priority of legislation that considers a gender perspective. More specific findings show that structural male dominance and cultural patriarchy within political parties systematically hinder affirmative policies. The results of the discourse analysis also show that media discourse consistently reproduces gender stereotypes, positioning female politicians as symbolic or passive actors through certain lexical and framing choices. This is seen in the placement of women in symbolic roles, marginalization in non-strategic commissions, and lack of attention to important policies such as equal pay and gender-based violence, indicating that the transition from descriptive to substantive representation is still fundamentally hampered.